Integrated analysis of fish intestine biomarkers: Complementary tools for pollution assessment - Marinsek, Gabriela Pustiglione [UNESP]; Choueri, Paloma Kachel Gusso [UNESP]; Choueri, Rodrigo Brasil; de Souza Abessa, Denis Moledo [UNESP]; Gonçalves, Alexandre Rodrigo Nascimento [UNESP]; Bortolotto, Lorihany Bogo [UNESP]; de Britto Mari, Renata [UNESP] (Elsevier, 2022)
The gastrointestinal tract and its enteric nervous system are the first routes of food and xenobiotics uptake. Considering the importance of this organ, this study evaluated intestinal biomarkers of Sphoeroides testudineus integrating the data to generate tools for pollution assessment. The fish were collected in three sites of São Paulo Coast and their intestines were analyzed for biochemical, histology, and neuronal density and morphometry biomarkers. To evaluate the differences among the data, a PERMANOVA was applied, followed by a FA/PCA. The PERMANOVA indicated differences (P < 0.001) between the regions (RA, A1, and A2). Four factors were extracted from the FA/PCA (62% cumulative), showing that the animals from A2 presented severe alterations, mainly in intestinal morphometry and neuronal density. A1 alterations refer mainly to the increase of neuronal metabolism. Our results also evidence a gradient of environmental quality related to the protection level (AR > A1 > A2).
Keywords: Biochemical biomarkers; Enteric nervous system; Histology; Morphophysiological biomarkers